Frequency of TORCH infection among the donor population in the republican center for blood transfusion - Samatova L.D.; Saidov A.B.; Bobozhonova Sh.D.; Kuchkarova Kh.R. (E3S Web of Conferences, 2023)
In this study, we analyzed the frequency of TORCh infections (CMV, toxoplasmosis, rubella and herpes viruses) among donors at the Republican Blood Transfusion Center. This finding is useful for understanding the prevalence of TORCh infections among donors. Among donors, this study was conducted for the first time. To determine the presence of TORCH infection in the blood serum, enzyme-linked immunosorbent assay (ELISA) was performed, and specific IgG antibodies (immunoglobulin G) were determined in the blood serum. The presence of IgG antibodies (to a specific disease) indicates a long course of infection and the formation of immunity against it.